A Study on Use of Plastic Coated Aggregates (PCA) in Bituminous Concrete Mixes of Flexible Pavement - Mishra, Brajesh; K. Gupta, M. (International Journal of Engineering and Technology, 2018)
The continuous increase in road traffic and heavy loading in combination with insufficient maintenance due to paucity of funds has resulted in deterioration of road network in India. To improve this proper maintenance, effective and improved roadway design, use of better quality materials and use of effective and modern construction techniques should be put into practice. During last three decades in many countries around the world it has been tested that modification of the bituminous binder with plastic/polymer additives enhances the properties and life of bituminous concrete pavements. The present investigation was carried out to propose the use of plastic coated aggregate (PCA) in bituminous mix of flexible pavements in order to improve their performance and also to give a way for safe disposal of plastic wastes in order to counter environmental pollution as well. There are mainly two processes available for incorporation of waste plastic in bituminous concrete mixes namely wet and dry process.  In this study the dry process was used for bituminous concrete mixes as it being simple and economical. Physical properties of conventional and plastic coated aggregates were compared. The Marshall method of mix design was adopted using VG-10 grade bitumen for conventional aggregates and plastic coated aggregates (PCA). Marshall Specimens were prepared at bitumen content ranging from 4% to 6% with a increment of 0.5% by weight of aggregates and with waste plastic content of 5%, 7%, 9%, 11%, 13% and 15% by weight of optimum bitumen content. Marshal stability, Flow value,  Air voids (Vv), Voids in mineral aggregates (VMA), and Voids filled with bitumen(VFB) were determined and compared with conventional aggregates (without plastic) bituminous concrete mixes. It was found that there was a reduction in consumption of bitumen in bituminous concrete mix by use of plastic coated aggregates also a considerable improvement in the properties of aggregates and bituminous concrete mix leading to provide longer life and improved pavement performance.